Gadget Addiction and the Students’ Achievement - Barotun Mabaroh; Lilik Sugianti (International Journal of Social Learning (IJSL), 2021)
Using gadgets cannot be avoided in daily life. It becomes more primary for students in higher education since they change to learn online during the covid−19 pandemic period. They should use gadgets focusing on education, but unfortunately, studies had reported that students are addicted to using gadgets to access some entertaining applications. Therefore, it was essential to investigate how the students manage using gadgets and their effects on their achievement. This survey research required the student's responses to a Gadget Scale-Short Version (SAS-SV) Addict item. The researchers collected data using a survey questionnaire on Google Form to determine how using gadgets affects the students' achievement. This research was done from August to December 2020. The results showed that both male and female students were identified as high-risk addicted. Moreover, the gadget addiction had terrible effects on the student's physical and psychological even though it did not significantly impact their academic achievement. However, based on the results, it was hoped that there should be the best management for using gadgets to improve the students’ achievement and prevent the long-term risk of gadget addiction.